Didactic Conditions For The Development Of Creative Abilities Of Future Primary School Teachers (Journal of Pedagogical Inventions and Practices, 2026)
This article analyzes the didactic conditions for the development of creative abilities of future primary school teachers from a theoretical and pedagogical perspective, and highlights the issue of forming the creative potential of future teachers in the context of the increasing need for creative pedagogical personnel in the modern education system, the priority of the competency-based approach, and the development of innovative educational technologies, the psychological and pedagogical content of the concept of creativity, its structural components, and didactic factors that develop students' creative abilities, the importance of problem-based learning, interactive methods, digital learning environments, and the reflexive approach in developing creative thinking as a current pedagogical problem